2010
DOI: 10.1080/17455030903410398
|View full text |Cite
|
Sign up to set email alerts
|

Fractional precursors in random media

Abstract: When a broadband pulse penetrates into a dissipative and dispersive medium, phase dispersion and frequency-dependent attenuation alter the pulse in a way that results in the appearance of a precursor field with an algebraic decay. We derive here the existence of precursors in nondispersive, non-dissipative, but randomly heterogeneous and multiscale media. The shape of the precursor and its fractional power law decay with propagation distance depend on the random medium class. Three principal scattering precurs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…( 37) and the random effective propagation model Eq. ( 16) in Garnier and Sølna (2010). Näsholm and Holm (2011) considered the integral generalization…”
Section: Convolution Formulation Of the Multiple Relaxation Modelmentioning
confidence: 99%
“…( 37) and the random effective propagation model Eq. ( 16) in Garnier and Sølna (2010). Näsholm and Holm (2011) considered the integral generalization…”
Section: Convolution Formulation Of the Multiple Relaxation Modelmentioning
confidence: 99%
“…(24) and (25) are not specific to the Lorentz medium but have some generality [37]. They hold for the Debye medium [38], for some random media [39], and, more generally, whenever the transfer function of the medium can be expanded in cumulants and the propagation distance is such that |κ| 1. Stoudt et al [38] showed in particular that the results of their experiments on water (Debye medium) at decimetric wavelengths can be numerically reproduced by neglecting the group-delay dispersion, that is the approximation made to obtain the analytical result of the Eq.…”
Section: A Transfer Function H B (Zω) and Impulse Responsementioning
confidence: 99%